Can Acting Out Online Improve Adolescents’ Well-Being During Contact Restrictions? A First Insight Into the Dysfunctional Role of Cyberbullying and the Need to Belong in Well-Being During COVID-19 Pandemic-Related Contact Restrictions - Pfetsch, Jan S.; Schultze-Krumbholz, Anja; Lietz, Katrin (Frontiers in Psychology, 2022)
Connecting with peers online to overcome social isolation has become particularly important during the pandemic-related school closures across many countries. In the context of contact restrictions, feelings of isolation and loneliness are more prevalent and the regulation of these negative emotions to maintain a positive well-being challenges adolescents. This is especially the case for those individuals who might have a high need to belong and difficulties in emotional competences. The difficult social situation during contact restrictions, more time for online communication and maladaptive emotion regulation might lead to aggressive communication patterns in the form of cyberbullying perpetration. In an online study with N = 205 adolescents aged 14 to 19 (M = 15.83, SD = 1.44; 57% girls, 31% boys), we assessed the frequency of online and offline contacts, need to belong, emotion regulation problems, feelings of loneliness and cyberbullying perpetration as predictors of adolescents’ well-being. In particular, we explored whether cyberbullying perpetration might function as a maladaptive strategy to deal with feelings of loneliness and therefore predicts well-being. This effect was expected to be stronger for those with a higher need to belong and with higher emotion regulation problems. Results of a hierarchical regression analysis revealed that well-being was significantly predicted by less emotion regulation difficulties, less feeling isolated and more cyberbullying perpetration. We also tested whether the need to belong or emotion regulation problems moderated the association between cyberbullying and well-being. While the results for emotion regulation problems were not significant, the moderation effect for the need to belong was significant: For students with a high need to belong, well-being was more strongly related to cyberbullying perpetration than for students with a medium need to belong. For students with a low need to belong, cyberbullying was not significantly associated with well-being. That cyberbullying perpetration predicted well-being positively is rather surprising in the light of previous research showing negative psychosocial outcomes also for cyberbullying perpetrators. The moderation analysis provides a hint at underlying processes: In times of distance learning and contact restrictions, cyberbullying may be a way of coming into contact with others and to regulate loneliness maladaptively.